Sistem Pendukung Keputusan Penetapan Karyawan Teladan Menggunakan Metode MAUT - Lase, Devi Lestari (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2024)
The large number of consumers of bird's nests has succeeded in attracting the interest of several people to set up a bird's nest business because it provides quite large profits. The important activities that employees must carry out in the swallow's nest business are: scraping, applying special medicine to swallow's nests, plucking, washing, drying, sorting, printing, packing, and then marketing. The problem that occurs in the process of determining Q'nest's exemplary employees is the difficulty of making decisions quickly and accurately. The process of determining Q'nest's exemplary employees often finds errors in determining exemplary employees. Where field supervisors are less thorough and effective in collecting employee data so that the employees selected are not suitable or worthy of being model employees. The results of the calculation of Q'nest's exemplary employee who ranked first or the highest score was 102.6 in the name of Riswati Sembiring. From the results of this research, it can be concluded that users of the decision support system in evaluating Q'nest exemplary employees using the MAUT method can enable effective and efficient evaluation and make it easier for companies to determine Q'nest exemplary employees. Determining Q'nest's exemplary employees can increase institutional incentives to improve other companies.